Perceived Reciprocity and Well‐Being at Work in Non‐Professional Employees: Fairness or Self‐Interest?. (28th January 2012) - Moliner, Carolina; Martínez‐Tur, Vicente; Peiró, José M.; Ramos, José; Cropanzano, Russell
Abstract This article assesses the links between non‐professional employees' perceptions of reciprocity in their relationships with their supervisors and the positive and negative sides of employees' well‐being at work: burnout and engagement. Two hypotheses were explored. First, the fairness hypothesis assumes a curvilinear relationship where balanced reciprocity (when the person perceives that there is equilibrium between his/her efforts and the benefits he/she receives) presents the highest level of well‐being. Second, the self‐interest hypothesis proposes a linear pattern where over‐benefitted situations for employees (when the person perceives that he/she is receiving more than he/she deserves) increase well‐being. One study with two independent samples was conducted. The participants were 349 employees in 59 hotels (sample 1) and 690 employees in 89 centres providing attention to people with mental disabilities (sample 2). Linear and curvilinear regression models supported the self‐interest hypothesis for the links from reciprocity to burnout and engagement. We conclude with theoretical implications and opportunities for future research. Copyright © 2012 John Wiley & Sons, Ltd.